Mortality Predictors in Trauma Patients in an Indonesian Emergency Department: A Retrospective Cohort Study - Widiyawati, Kholisah; Lestari, Retno; Suryanto , Suryanto (Journal of Applied Nursing and Health, 2025)
Background: especially in low- and middle-income nations. Identifying mortality-related factors in trauma patients is essential to enhance early management and reduce death rates. This retrospective cohort study follows the STROBE guidelines and analyzes factors associated with mortality among trauma patients in the emergency department (ED) of a resource-limited setting. Methods: This study included 356 trauma patients who presented to the ED of Bina Sehat Hospital in Jember between February 2023 and February 2025. Data were collected from electronic medical records. The variables assessed included age, gender, mean arterial pressure (MAP), systolic blood pressure, oxygen saturation, Glasgow Coma Scale (GCS), mechanism of trauma, and Revised Trauma Score (RTS). Bivariate and multivariate logistic regression analyses were conducted. A flow diagram was used to depict participant selection, and missing data were excluded listwise. Inter-rater agreement was ensured through standardized training of data collectors.. Results: Of 356 patients, 88.5% survived and 11.5% died. Bivariate analysis indicated that age, oxygen saturation, GCS, and RTS were significantly related to mortality (p < 0.001). Multivariate analysis identified that a low RTS (p = 0.002), a low GCS (p < 0.001), and high MAP (p = 0.041) were independent predictors of mortality. The RTS had the strongest association with mortality, reducing odds by 91.8% per unit increase. Conclusion: RTS is the most robust predictor of mortality in trauma patients in this resource-limited ED setting. Implementing RTS in triage protocols may enhance early risk identification and guide targeted interventions. A multicenter validation is recommended.